Pengaruh Media Pohon Aksara terhadap Hasil Belajar Siswa Mata Pelajaran Bahasa Jawa Kelas IV SD - Dian Ervina Widiastuti; Djoko Hari Supriyanto; Sofyan Susanto (Universitas Muhammadiyah Enrekang, 2021)
In the implementation of this research, it was found that there are still many obstacles faced by students, the background of this research is the lack of student learning outcomes in studying Javanese script and the low understanding of students in learning Javanese script so that the learning achievement of fourth grade students is lacking. In this research, the method used is quantitative method with experimental type with pretest posttest nonequilvalent group design design. Collecting data in the form of observations, tests and documentation. The tests used are pretest and posttest. The population of this study were fourth grade students of SDN Karangbanyu 3 with fourth grade students of SDN Sidolaju 3 and used samples of IV B control class and IV A experimental class. The prerequisite test used is the homogeneity test to see the similarities between the two groups and the data analysis technique using the independent sample t-test test was tested with SPSS 17.0 software. The results of this study show the difference between the experimental class and the control class, including the average value the experimental class posttest was 73.89 and the average value of the control class was 70.90 while the t-test of the experimental class posttest resulted in a Sig value. (2 tailed) 0.003 < 0.05 and the control class posttest value resulted in a Sig. (2 tailed) 0.002 <0.05 so it can be concluded that there is a difference between the experimental class and the control class, so Ha is accepted and H0 is rejected. From the results of the overall research data, the media script tree is effective in improving learning outcomes of Javanese script in fourth grade elementary school.